STATUS GIZI DAN STATUS TANDA VITAL MAHASISWA AKFIS UKI - Weeke Budhyanti (Jurnal Pro-Life, 2018)
Since 2007, Indonesia has been declaring war with malnutrition which are roots of health problems. Research was conducted to found out nutritional status distribution of Akfis UKI students as a preliminary research to evaluate and improving their health status. Research conducted as qualitative descriptive of height, weight and body mass index of 127 persons. Research shown that of Akfis UKI students found 29.9% were stunted; 10.22% obesity; 5% overweight; 19.66% wasted and 3.14% severely wasted. Body mass index’ data correlated with vital signs data of the same students, which are 1.81% hypotension student; 8.17% prehypertension; 3.62% hypertension, dan 21% tachycardia. Correlation of nutritional and vital sign status is 0.11. Therefore, no correlation between body mass index and vital signs. Keywords : body mass index, obesity, wasted